IMPLEMENTASI GAME BAHASA MODEL UJI PENGETAHUAN UNTUK MENINGKATKAN PENGUASAAN KOSA KATA BAHASA ARAB - Wardani Wardani; Almanna Wassalwa (Fakultas Tarbiyah Universitas Ibrahimy, 2020)
This research is to describe the implementation of the knowledge test language game model to improve the ability of Arabic vocabulary in the Arabic Language Development Institute (LPBA) in Salafiyah Syafi'iyah Islamic Boarding School Sukorejo Situbondo East Java, Academic Year 2014-2015. By using a qualitative approach to the type of case study research. The method of collection data technique uses the interviews, observation, and documentation. With data analysis namely data reduction, data description, and conclusions. Based on the results of the analysis, it can be concluded that: the implementation of the language game with the knowledge test model to improve the ability of Arabic vocabulary is sufficient and competent by providing direction and guidance, fostering learning motivation for members to reward outstanding members and all things that can support towards the smooth teaching and learning process. such as the use of audio-visual media so that effective and motivative learning is created; and factors that can influence improving Arabic vocabulary mastery in the Institute of Arabic Language Development (LPBA) Salafiyah Syafi'iyah Sukorejo Islamic Boarding School in Situbondo East Java is clarified into two types, namely: consists of internal factors, such as the ability to think and external factors such as the encouragement of parents and teachers.